Yttria-zirconia-based lewis acid catalysis of the biginelli reaction: an efficient one-pot synthesis of 3,4-dihydropyrimidin-2-(1H)-ones - Ramalingam, S.; Kumar, Pradeep (Synthetic Communications, 2009)
Yttria-zirconia-based Lewis acid efficiently catalyzes the three-component cyclocondensation reaction of aldehyde, -keto ester, and urea or thiourea in refluxing acetonitrile to produce the corresponding dihydropyrimidones in high yields.
Keywords: Biginelli reaction; dihydropyrimidone; yttria-zirconia-based Lewis acid